Influence of Isometric Exercise Combined With Electromyostimulation on Inflammatory Cytokine Levels, Muscle Strength, and Knee Joint Function in Elderly Women With Early Knee Osteoarthritis - Park, Sunhee; Min, Sukyung; Park, Si-Hwa; Yoo, Jaehyun; Jee, Yong-Seok (Frontiers in Physiology, 2021)
Background and objectives: Muscle strengthening exercise is suggested to beneficial for patients with knee osteoarthritis (OA) and electrical muscular stimulation is reported to be effective in improvement of muscle strength. This study examined whether isometric exercise combined with whole body-electromyostimulation (WB-EMS) can improve serum cytokine levels, muscle strength, and knee function in elderly women with early knee OA. Materials and Methods: This randomized controlled study included 75 participants assigned into three groups: the control group (CON), isometric exercise group (ISOM), and isometric exercise and electromyostimulation group (ISOM+EMS). The two exercise groups performed their respective programs for 8 weeks, 3 days a week, 30 minutes a day. The main exercises for both groups were performed continuously during the 20 minutes in an alternation of a 6-s contraction with a 4-s break. At pre- and post-intervention, anthropometric variables, muscle strength, Knee Injury and Osteoarthritis Outcome Score (KOOS), and blood sampling for biomarkers including interleukin-6, tumor necrosis factor-α, C-reactive protein, and resistin were performed. Results: All variables at pre-intervention showed no significant differences among the three groups. However, there were significant differences between groups for body composition, muscle strength, KOOS subscale scores, and biomarkers. ISOM+EMS group resulted in a significant reduction in body weight, fat mass, fat percentage, inflammatory cytokine levels, and increased muscle strength. An ISOM+EMS group had the best KOOS score among all groups. Conclusions: Isometric exercise combined with WB-EMS resulted in the best overall improvements in knee function and alleviating the pain and symptoms of patients with early knee OA. Further, reduced levels of inflammatory cytokines were observed. These non-pharmacologic, non-invasive interventions should be considered by healthcare specialists for elderly patients with early knee OA.